AUGUSTINE ON MORAL CONSCIENCE - Svensson, Manfred (Heythrop journal, 2013)
There are widely differing accounts of Augustine's place in the early history of the notion of conscience. While some regard his contribution as groundbreaking, others consider that he only stressed interiority more than earlier authors. Starting with a contrast with Jerome, the present article aims at clarifying Augustine's specific contribution and the place of conscience in his moral thought.